HUBUNGAN PENGETAHUAN IBU HAMIL DENGAN KECEMASAN DALAM MENGHADAPI PERSALINAN SAAT PANDEMI COVID-19 - Darmiyanti, Ni Made; Oktaviani, Putu Vivin Frida (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2023)
Abstract: Coronavirus or corona virus is a large family of viruses that cause mild to moderate upper respiratory tract infections, such as flu. The method of spreading Covid-19 is the same as other viruses in general, such as: drooling someone with the infected person, touching the hands or face of an infected person, touching the eyes, nose or mouth after handling objects containing the virus. This study uses the correlation method (relationship) with a cross-sectional design. Data collection is carried out online via a link distributed through whatsap social media. Data analysis used Rank Spearman, with a sample size of 27 people. The results showed that there was a significant relationship between the knowledge of pregnant women about Covid-19 with the level of anxiety of pregnant women in facing childbirth during the Covid-19 pandemic with a sig. <0.05 with a strength level of 0.838, which means that the relationship is very strong and the relationship is unidirectional. The conclusion of this study is that there is a significant, very strong and unidirectional relationship between the knowledge of pregnant women about Covid-19 and the level of anxiety of pregnant women in facing childbirth during the Covid-19 pandemic with a sig <0.05. Abstrak: Coronavirus atau virus corona merupakan keluarga besar virus yang menyebabkan infeksi saluran pernafasan atas ringan hingga sedang, seperti penyakit flu. Cara penyebaran Covid-19 sama dengan virus lain pada umumnya, seperti: percikan air liur pengidap, menyentuh tangan atau wajah orang yang terinfeksi, menyentuh mata, hidung atau mulut setelah memegang benda yang mengandung virus. Penelitian ini menggunakan metode korelasi (hubungan) dengan rancangan crossectional. Pengambilan data dilakukan secara daring melalui link yang didistribusikan melalui sosial media whatsap. Analisa data menggunakan Rank Spearman, dengan jumlah sampel 27 orang. Hasil penelitian ada hubungan yang signifikan antara pengetahuan ibu hamil tentang Covid-19 dengan tingkat kecemasan ibu hamil dalam menghadapi persalinan saat pandemi Covid-19 dengan nilai sig.<0,05 dengan tingkat kekuatan hubungan 0,838 yang berarti hubungan sangat kuat dan hubungan bersifat searah. Kesimpulan penelitian adalah ada hubungan yang signifikan, sangat kuat dan searah antara pengetahuan ibu hamil tentang Covid-19 dengan tingkat kecemasan ibu hamil dalam menghadapi persalinan saat pandemi Covid-19 dengan nilai sig<0,05.